Filogeografia de um complexo de espécies de Phalloceros harpagos Lucinda, 2008 (Cyprinodontiformes: Poeciliidae). - Oliveira, Isadora Janolio de (2017)
Species are basic units for the understanding of biogeographic patterns that is why, its correct delimitation is essential. The group of fishes Poecilian is widely used as biological model, due to its congruence between distribution and diversification processes. In this case, the distribution of the species Phalloceros Eigenmann, 1907 is generally allopatric and restricted. On the other hand, Phalloceros harpagos presents a wide distribution and morphological variations between populations of different watersheds. Such characteristics make the hypothesis of a complex of cryptic species plausible. Samples of P. harpagos were collected in their catch basins, which include coastal basins from Espírito Santo to Santa Catarina and the upper Paraná River basin. Subsequently, the DNA was extracted for amplification and partial sequencing of the Mitochondrial COI gene. Delimitation for research was based in coalescence tests such as ABGD, PTP and GMYC. The molecular clock was calculated for phylogeographic inferences. The results indicated that P. harpagos correspond to a complex of species, represented by five phylogroups. The diversification of the groups began in the Miocene, resulting from the separation between Paraná and Paraíba do Sul river basins. Most of the phylogroups had a restricted distribution, such as the coastal basins of Santa Catarina, Rio de Janeiro, Espírito Santo and São Paulo. However, one group presented a wide distribution, occurring mainly in the Paraná, Ribeira de Iguape and Iguaçu river basins. This distribution may be a result of headwater captures events, which happened through a reactivation of failures and erosions in the quaternary. This paper suggests hypotheses about vicariance events and recent diversification processes in species level. Molecular dating information about the genus Phalloceros may contribute significantly in the suggestion of vicariance speciation events and other inferences for biogeography in South America.